Comprehensive Geriatric Health Assessment Core Competencies and Skills for Primary Care Nurses: A Scoping Review - Ioanna, Dimitriadou; Eloranta, Sini; Šteinmiller, Jekaterina; Saridi, Maria; Lundberg, Anna; Häger, Magdalena; Hjaltadottir, Ingibjorg; Skuladottir, Sigrun S.; Korsström, Nina; Mört, Susanna; Tuori, Hannele; Fradelos, Evangelos C. (MDPI AG, 2025)
Objective
This scoping review aims to explore and synthesize the core competencies and skills required for primary care nurses conducting comprehensive geriatric assessments. Comprehensive geriatric assessments have become integral to providing holistic, patient-centered care for older adults with complex health needs, but the specific competencies required in primary care remain underresearched.
Design
​​​​​​​The review followed Arksey and O’Malley’s five-stage scoping review framework, incorporating studies from PubMed, CINAHL, EMBASE, and the Cochrane Library. A comprehensive search was conducted from May 2014 to May 2024, and a population–concept–context (PCC) framework was used to identify relevant studies.
Results
Nineteen studies met the inclusion criteria, revealing six key competency domains for nurses involved in comprehensive geriatric assessments: Clinical Assessment and Diagnostic Competencies, Care Planning and Coordination, Professional and Interpersonal Competencies, Environmental and Systemic Competencies, Technical and Procedural Competencies, and Quality Improvement and Evidence-Based Practice. These competencies are essential for providing high-quality care to older adults and supporting integrated, multidisciplinary approaches to geriatric care.
Conclusions
The identified competency domains provide a structured framework that can enhance primary care nurses’ ability to deliver more effective, individualized, and coordinated care to older adults. However, the standardization of these competencies remains crucial for ensuring consistency in practice.